Barriers to Behavior Change in Parents With Overweight or Obese Children: A Qualitative Interview Study - Ziser, Katrin; Decker, Stefanie; Stuber, Felicitas; Herschbach, Anne; Giel, Katrin Elisabeth; Zipfel, Stephan; Ehehalt, Stefan; Junne, Florian (Frontiers in Psychology, 2021)
Overweight and obesity among children and adolescents are a global problem of our time. Due to their authority and role modelling, parents play an essential part in the efficacy of prevention and intervention programs. This study assessed the barriers of parents of overweight/obese children for preventive and interventional health care utilization. N = 16 Parents were qualitatively interviewed. A content analysis was performed and barriers for change were allocated to their stage of change according to the transtheoretical model. Among the main barriers is the underestimation of health risks caused by overweight/obesity in association with diminished problem awareness. Parents seem not necessarily in need of theoretical knowledge for prevention and interventions. They do however need support in evaluating the weight status of their child, knowledge of whom to turn to for help as well as specific and hands-on possibilities for change. The results extend past studies by adding specific barriers to change parents commonly experience. Possibilities to address these barriers, e.g. through trainings at the pediatric practice or adoption of conversation techniques are discussed. Future studies might identify subgroups experiencing specific barriers and thus be able to address these in an individualized way.